Cohort Patient Evaluation of Lung Condition 9 Months after Severe Covid 19 - Mahendra, Reza Aditya; Rakhma , Sastia; Sugiri, Yani Jane Rosihaningsih; Djajalaksana, Susanthy; Erawati, Dini Rachma (Malang Respiratory Journal, 2025)
Introduction: COVID-19 is an infection caused by novel coronavirus Serious Acute Respiratory Syndrome (SARS)-CoV-2. About 20% patients with severe symptoms could become critically ill. In this case report, we present a case with severe COVID-19 infection. Case report: Mr. SA, a 54-year-old patient came to the hospital with chief complaint of dry cough. Patient had fever for 2 days and myalgia. Patient had a history of well-controlled hypertension. X-ray examination showed worsening consolidation and CT-scan showed pleural effusion. Patient was treated with convalescent plasma therapy, IVIG, and symptomatic drugs. The patient was diagnosed with confirmed case of severe COVID-19, stage I hypertension, hypercoagulable state, CCS, and grade I obesity. The Evaluation of this patient consist of CT Scan, Lung Function using a Body Plethysmograph that will followed for 9 month after the patient discharged. Conclusion: There had been a few therapeutic options for COVID-19 but no definitive treatment yet. IVIG and convalescent plasma had been used for the treatment of SARS-CoV and MERS-CoV. As such, these treatments were also used in COVID-19 treatment with promising results. Keywords: COVID-19, IVIG, convalescent plasma